FDG-PET-based neural correlates of Addenbrooke’s cognitive examination III scores in Alzheimer’s disease and frontotemporal degeneration - Cabrera-Martín, María Nieves; Nespral, Pedro; Valles-Salgado, Maria; Bascuñana, Pablo; Delgado-Alonso, Cristina; Delgado-Álvarez, Alfonso; Fernández-Romero, Lucía; López-Carbonero, Juan Ignacio; Díez-Cirarda, María; Gil-Moreno, María José; Matías-Guiu, Jorge; Matias-Guiu, Jordi A. (Frontiers in Psychology, 2023)
Introduction. The Addenbrooke’s Cognitive Examination III (ACE-III) is a brief test useful for neuropsychological assessment. Several studies have validated the test for the diagnosis of Alzheimer’s disease (AD) and frontotemporal dementia (FTD). In this study, we aimed to examine the metabolic correlates associated with the performance of ACE-III in AD and behavioral variant FTD. Methods. We enrolled 300 participants in a cross-sectional study, including 180 patients with AD, 60 with behavioral FTD (bvFTD), and 60 controls. An 18F-Fluorodeoxyglucose positron emission tomography study was performed in all cases. Correlation between the ACE-III and its domains (attention, memory, fluency, language, and visuospatial) with the brain metabolism was estimated. Results. The ACE-III showed distinct neural correlates in bvFTD and AD, effectively capturing the most relevant regions involved in these disorders. Neural correlates differed for each domain, especially in the case of bvFTD. Lower ACE-III scores were associated with more advanced stages in both disorders. The ACE-III exhibited high discrimination between bvFTD vs HC, and between AD vs HC. Additionally, it was sensitive to detect hypometabolism in brain regions associated with bvFTD and AD. Conclusions. Our study contributes to the knowledge of the brain regions associated with ACE-III, thereby facilitating its interpretation, and highlighting its suitability for screening and monitoring. This study provides further validation of ACE-III in the context of AD and FTD.